Citizen survey 1987 - Main survey - Westholm, Anders; Petersson, Olof (Uppsala University, 1995)
This survey forms part of the report on power ´Maktutredningen´, and deals with the citizen´s possibilities to influence. To study the citizen´s possibilities to affect hers/his own situation six different areas of life were chosen. Questions concerning the citizen´s role as a resident dealt with type of housing, participation in meetings or other activities arranged by tenants´ association or similar, activities together with neighbours, possibilities to affect housing conditions, reason for discontent in regard to housing during the last year, activities to accomplish improvements/counteract impairment, and if the demands were met. The role as a consumer were illustrated by questions concerning purchases of capital goods during the last year, possibilities to estimate the quality, choose between different manufactures, and to determine whether the purchase was the best value for money, discontent in regard to purchases during the last year, attempt to get adjustments, and if the demands were met. Questions about health and medical care dealt with own experience of medical care, concerning light illness, serious illness, hospital treatment, and the need for treatment of close relative, possibilities to affect the treatment, to get enough treatment, to choose doctor or change to another surgery or clinic, reason for discontent concerning medical treatment, activities to accomplish improvements/counteract impairment, and if the demands were met. Another area concerned family, with questions dealing with marital status, number of children and their age, household composition. Respondents married or cohabiting had to answer questions concerning their own possibility to affect major purchases for the family or the house, distribution of the housework, time spent together with family, how to raise the children, and how often she/he and the partner are of different opinion. Respondents with children aged 0-6 years were asked about child daycare, kind of child daycare used by the respondent, any longer talk with persons taking care of the child at the daycare center etc. during the last year, and with other parents having their children at the same place, or any activities together with other parents, possibilities to influence the disposition of the activities, the environment, the way the children are acting together, possibilities to change to another form of daycare and to get the right amount of daycare, reason for discontent in regard to child daycare, activities to accomplish improvements/counteract impairment, and if the demands were met. Respondents with children aged 7-15 years were asked about school, if one during the last year had attended meetings at school, other contacts with teachers, parent-teacher association, or other parents, about schooling, possibilities to influence the disposition of the education, the environment, the way the children act together, possibilities to change to another school, reason for discontent in regard to the conditions at the school, activities to accomplish improvements/counteract impairment, and if the demands were met. Questions regarding occupation and education dealt with possibilities to influence working hours, disposition of work, work environment, the general direction of work, to change to other tasks or to another employer, to influence the local union, the possibilities of the local union to influence the working conditions, reason for discontent in regard to the conditions at work, activities to accomplish improvements/counteract impairment, and if the demands were met. Questions concerning organizational activities, leisure time, and society dealt with groups most entitled to keep the job, differences in income, solidarity with various organizations and movements, political party, commissions of trust, interest in politics, party most liked, own political activities, church attendance, leisure-time activities, activities to accomplish improvements/counteract impairment in the community.

Purpose:

Aims to study the ability of citizens to influence their own situation and to participate in social decision-making.

Denna undersökning ingår som en delundersökning i Maktutredningen och handlar om medborgarnas möjligheter att påverka. För den del av studien som rör möjligheter att påverka sin egen situation har sex livsområden valts ut, representerande olika medborgarsituationer.

De frågor som berör rollen som boende handlar om vilken typ av bostad man har; om man deltagit i möten eller andra aktiviteter anordnade av hyresgästförening eller liknande; aktiviteter tillsammans med grannar; möjligheter att påverka boendet; anledning till missnöje beträffande boendet under det senaste året; aktiviteter för att åstadkomma förbättringar/motarbeta försämringar och om önskemålen blev tillgodosedda.

Rollen som konsument belyses genom frågor om inköp av kapitalvaror under senaste året; möjligheter att bedöma varans kvalitet, välja mellan olika fabrikat samt avgöra om den inköpta varan var mest prisvärd; missnöje med inköp under senaste året, försök att få rättelse och om önskemålen blev tillgodosedda.

Frågor om hälso- och sjukvård gällde egen erfarenhet av sjukvården beträffande lindrig sjukdom respektive allvarlig sjukdom; sjukhusvistelse eller nära anhörigas vårdbehov; möjligheter att påverka vården, få tillräcklig vård, välja läkare och byta till annan mottagning eller vårdklinik; anledning till missnöje med vården, aktiviteter för att åstadkomma förbättringar/motverka försämringar och om önskemålen blev tillgodosedda.

Ett annat område gällde familjen och dessa frågor handlade om civilstånd, antal barn, hushållets sammansättning och eventuella barns ålder. Gifta och samboende fick besvara frågor om den egna möjligheten att påverka större inköp till familjen eller hemmet; hushållsarbetets fördelning; tid ägnad åt familjen; hur barnen skall uppfostras och hur ofta det händer att man har olika uppfattningar.


Respondenter med barn i förskoleåldern fick besvara frågor om barntillsyn; hur man själv ordnat med barntillsynen; om man under det senaste året haft något längre samtal med den som passar barnet; om man haft längre samtal med andra föräldrar som har sin barntillsyn på samma ställe; om man deltagit i gemensam aktivitet med andra föräldrar som har sin barntillsyn på samma ställe; om man har förtroendeuppdrag eller varit med att anordna gemensam aktivitet tillsammans med föräldrar som har sin barntillsyn på samma ställe; möjligheter att påverka barntillsynens uppläggning och utformning, den miljö barnen vistas i, och det sätt på vilket barnen umgås med varandra; möjlighet byta till annan tillsynsform och att få barntillsyn i den omfattning man önskar; anledning att känna missnöje med förhållanden som rör barntillsynen, aktiviteter för att åstadkomma förbättringar/motverka försämringar och om önskemålen blev tillgodosedda.


Respondenter med barn i skolåldern fick besvara ett antal frågor om skola; om man under senaste året varit på föräldramöte eller kvartssamtal; kontakt med lärare eller skolledning på annat sätt; kontakt med hem- och skolaförening; kontakt med andra föräldrar angående barnens skolgång; om man varit klassmamma/klasspappa; möjligheter att påverka undervisningens uppläggning och utformning, skolmiljöns utformning, sättet på vilket eleverna umgås med varandra i skolan; möjligheter att byta till en annan skola; anledning till missnöje med förhållanden i barnets skola, aktiviteter för att åstadkomma förbättringar/motverka försämringar och om önskemålen blev tillgodosedda.


Frågor om arbete och utbildning gällde det egna förvärvsarbetet; möjligheter att påverka arbetstidens förläggning; arbetets uppläggning; arbetsmiljön; arbetets allmänna inriktning; byta till andra arbetsuppgifter eller annan arbetsgivare; påverka det lokala fackets agerande; fackets möjligheter att påverka förhållandena på arbetsplatsen; anledning att känna missnöje, aktiviteter för att åstadkomma förbättringar/motverka försämringar och om önskemålen blev tillgodosedda.
Frågor om föreningsliv, fritid och samhälle gällde bland annat vilka grupper som främst bör få behålla jobbet vid uppsägningar; inkomstskillnader; samhörighet med olika sammanslutningar och rörelser; medlemskap i organisationer och sammanslutningar, politiskt parti; politiska uppdrag; intresse för politik; bästa parti; deltagande i offentlig demonstration; anförande och diskussionsinlägg; skrivit insändare eller artikel; gudstjänstbesök; fritidsaktiviteter; aktiviteter för att åstadkomma förbättringar/motverka försämringar i samhället.


Respondenterna fick också ta ställning till ett antal påståenden om förhållandena i Sverige idag; egenskaper för att vara en god medborgare; förtroende för olika grupper i samhället; samt göra en bedömning av hur väl ett antal beskrivningar av olika sorters personligheter stämmer in på sig själv.


Huvudundersökningen grundas på ett urval som representerar i riket bosatta vuxna personer. Detta material kompletteras av ett speciellt delurval av gifta par, vilket gör det möjligt att analysera familjens politiska arbetsfördelning. Frågan är om familjerna är homogena eller heterogena, huruvida endast den ene av makarna eller båda makarna engagerar sig i samhällslivet.

Syfte:

Syftar till att undersöka medborgarnas möjligheter att påverka sin egen situation samt att delta i det samhälleliga beslutsfattandet.
Medborgarundersökningen 1987 - Huvudundersökningen
MBU87
Keywords: housing; boende; participation; deltagande; children; barn; religious attendance; religiöst deltagande; housework; hushållsarbete; job satisfaction; arbetstillfredsställelse; trust; förtroende; domestic responsibilities; hushållsansvar; child care; barnomsorg; citizenship skills; medborgerliga färdigheter; family life; familjeliv; shopping; shopping; workplace; arbetsplats; health services; hälsovård; schools; skolor; working conditions; arbetsförhållanden; households; hushåll; clubs; föreningar; Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Housing; Bostäder; Working conditions; Arbetsförhållanden; Equality, inequality and social exclusion; Jämlikhet, ojämlikhet och socialt utanförskap; Family life and marriage; Familjeliv och äktenskap; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap